2018
DOI: 10.21547/jss.444386
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stance Lexical Bundles by Turkish and Japanese EFL Learners and Native English Speakers in Academic Writing

Abstract: Linguists have been interested in the sequences of words that tend to occur for a long time. The present study examines a particular type of recurrent chunks called lexical bundles (LB). LBs are multi-word expressions and an important component of the fluent linguistic production depends on the control of them (Hyland, 2008a). The purpose of this study was to find out the most common stance LBs used in argumentative essays written by native English speakers and Turkish and Japanese EFL learners. It also aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The results were consistent with Öztürk (2014), who found that LBs were employed more frequently by Turkish researchers against L1. However, Muşlu (2018) found that L1 English corpus was more varied than L2 English corpus in terms of LB usage. We conducted LL statistics to calculate whether the difference of frequency counts in the two corpora was statistically significant.…”
Section: Findings and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results were consistent with Öztürk (2014), who found that LBs were employed more frequently by Turkish researchers against L1. However, Muşlu (2018) found that L1 English corpus was more varied than L2 English corpus in terms of LB usage. We conducted LL statistics to calculate whether the difference of frequency counts in the two corpora was statistically significant.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…It is likely that L2 English writers may not have a clear understanding of the functions of bundles. A study conducted by Muşlu (2018) showed that while there was a heavy reliance on LBs by Japanese and Turkish writers, L1 English writers did not have a tendency towards employing such bundles frequently in their argumentative essays. Karabacak & Qin (2013) compared the argumentative essays written by Turkish, Chinese, and American students with an academic writing corpus taken from the New York Times magazine.…”
Section: Research In Lexical Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin (2019) conducted a study between L1 and L2 writers, observing that both groups used similar recurrent expressions such as frequently used verb phrase expressions, stance expressions and prepositional phrase expressions. Muşlu (2018) conducted research on the usage of four-word stance recurrent expressions among Turkish and Japanese EFL learners in comparison with native writers and concluded that L2 writers showed overuse patterns with higher frequency. However, different from the present study, verb phrase expressions were the mostly used expression type.…”
Section: Tr(f) Eng (F)mentioning
confidence: 99%
“…Language researchers are becoming increasingly interested in the study of the lexical bundle, which has become a challenging research area [11]. They are extended collocations that unpredictably appear more often than would be expected by chance, shaping meanings in certain contexts and improving our perception of text coherence [12]. A lexical bundle is a repeated grouping of three or more words that is typically referred to as a chunk or cluster (Hyland, 2008, p. 5).…”
mentioning
confidence: 99%